2014
DOI: 10.3109/00952990.2014.907302
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of binge drinking and associated co-factors among medical students in a US Jesuit University

Abstract: Binge drinking was highly prevalent among the sampled medical students, especially during an after-exam party. Identifying healthy coping strategies among medical students is warranted to reduce binge drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 32 publications
4
25
0
7
Order By: Relevance
“…Our study is consistent with previous research suggesting that many medical students use illicit drugs [6,7] and drink heavily [4,5]. Our findings also indicate that substance use during medical school often impacts students’ personal and professional lives.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Our study is consistent with previous research suggesting that many medical students use illicit drugs [6,7] and drink heavily [4,5]. Our findings also indicate that substance use during medical school often impacts students’ personal and professional lives.…”
Section: Resultssupporting
confidence: 92%
“…Comparatively, those in the general population with ages ranging from 18–25 and 26 and older reported rates of alcohol use within the past month at 59.6% and 56.5% respectively [1], which is notably lower than medical students of similar ages in this investigation. Consistent with other studies, we found that male medical students tend to consume significantly more alcohol than their female peers [4]. This pattern remained when comparing our sample to age matched peers in the general population; both male (87.8%) and female medical (83.9%) students in the current sample consumed alcohol in the past 30 days at higher rates than male (72.8% of 21–25 year olds; 69.3% of 26–34 year olds) and female (65.4% of 21–25 year olds, 59.7% of 26–34 year olds) respondents in the general population [18].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations